(untitled) (Journal of Universal Science Research, 2024)
Clinical laboratory testing plays a pivotal role in modern healthcare by providing essential data for diagnosing diseases, monitoring patient health, and guiding treatment decisions. This article examines the importance of laboratory diagnostics in improving patient outcomes, emphasizing its role in chronic disease management, infectious disease control, and treatment efficacy. Furthermore, the article explores the technological advancements in laboratory testing and their impact on precision medicine. Despite its critical role, laboratory testing also faces challenges such as test accuracy, interpretation, and accessibility, which are discussed alongside potential solutions.